The New Topology of Multilevel Inverter with Less Number of Switches (International Journal of Innovative Research in Computer Science & Technology, 2021)
A new multilayer inverter topology is  proposed in this study. The cascaded feature is used in this  innovative topology. In addition to the isolated DC sources  seen in Cascaded H- bridge. The clamping diode in Diode  and the multilevel inverter (CHB-MLI) Inverter with  Clamped Multilevel (DC-MLI). With these advantages, an  inverter topology with 18 total component counts when  coupled had been discovered. This proposed topology has  the potential to generate up to According to the ratio  allocated to its DC sources, there are 17 output levels.  Aside from increasing the number of output voltage levels,  this study has a relatively low number of component  counts. The THD limit defined by IEEE standard is also a  goal (i.e. 5 percent) all voltage applications under 69kV.  To ensure that the suggested topology is functional, it is  being simulated in Mat lab/Simulink with various  modulation indexes. The amount of THD, the number of  voltage outputs, and the RMS voltage are all being  monitored and discussed. Finally, to assess the uniqueness  of the suggested topology, a comparison study with  recently disclosed topologies is being carried out.
Keywords: Multilevel Inverter; Switches; DCMLI; FCMLI; CHBMLI; Thottempudi Prasanth